Identification of Molecular Markers That Are Specific to the Class Thermoleophilia - Hu, Danyu; Zang, Yang; Mao, Yingjin; Gao, Beile (Frontiers in Microbiology, 2019)
The class Thermoleophilia is one of the deep-rooting lineages within the Actinobacteria phylum and metagenomic investigation of microbial diversity suggested that species associated with the class Thermoleophilia are abundant in hot spring and soil samples. However, very few species of this class have been cultivated and characterized. Our understanding of the phylogeny and taxonomy of Thermoleophilia is solely based on 16S rRNA sequence analysis of limited cultivable representatives, but no other phenotypic or genotypic characteristics are known that can clearly discriminate members of this class from the other bacteria. This study reported phylogenomic analysis for 12 sequenced members of this class and clearly resolved the interrelationship of uncultivable species with reconstructed genomes and known type species. Comparative genome analysis discovered 12 CSIs in different proteins and 32 CSPs that are specific to all species of this class. In addition, a large number of CSIs or CSPs were identified to be unique to certain lineages within this class. This study represents the first and most comprehensive phylogenetic analysis of the class Thermoleophilia, and the identified CSIs and CSPs provide valuable molecular markers for the identification and delineation of species belonging to this class or its subgroups.